Multi-species rotational grazing of small ruminants regenerates undergrowth vegetation while controlling weeds in the oil palm silvopastoral system - Tohiran, Kamil Azmi; Nobilly, Frisco; Zulkifli, Raja; Yahya, Muhammad Syafiq; Norhisham, Ahmad Razi; Rasyidi, Md Zainal; Azhar, Badrul (Elsevier, 2023)
CONTEXT Prolonged use of synthetic herbicides to control weeds may cause adverse effects on the environment and human wellbeing. As a mitigation effort, commercial oil palm growers have been encouraged to adopt livestock integration as a holistic approach to manage weeds. Previous studies have suggested utilizing a multi-species livestock grazing may optimize the grazing impacts in silvopastoral agroforestry systems.